EFEKTIVITAS EDUKASI GIZI MENGGUNAKAN MEDIA KOMIK TERHADAP PENGETAHUAN DAN SIKAP TENTANG GIZI SEIMBANG PADA SISWA SEKOLAH DASAR - Enggar Redyastuti; Wiwik Wijaningsih; Yuniarti Yuniarti; Meirina Dwi Larasati (JURNAL RISET GIZI, 2017)
Background  : Some issue found during preliminary survey and have not revealed the good dietary habit with balanced nutrient; for example: did not bring lunch and drink from home, buy unhealthy snack outside the school, and low knowledge about the importance of high protein side-dish, vegetables, and fruits. Nutrition education for elementary school students can support them to have good dietary habit. Using media can help us to give information.Objective  :  To know the influence of giving an education of balanced nutrient using media of comic-book with the content: knowledge and attitude of balanced nutrient to elementary school students.Methods  : This research is classified to community nutrition research. The type of research is quasi experimental design and the plan is design with the pretest - posttest control group design. Total sample is 72 students, divided into treated-group and control-group. Collected data are identity, pretest and posttest result of knowledge-and-attitude. The test method that be used are Independent t-test and Mann Whitney.Results  : Average score of knowledge in treated-group increased 6,36 points and in control-group 3,79 points. Average score of attitude in treated-group increased 0,98 points and in control-group 1,82 points.Conclusion  : There were significantimpact of giving nutrition education using media of comic-book towardsbalanced nutrition knowledge on elementary school students (p=0,017), while on the attitude the improvement is not significant, (p=0,549).